High-competence graduates have advantages in marketability - Mimi Rabita, Abdul Wahit (2022)
KUANTAN, 17 March 2022 - Graduates with high competence by mastering various languages, self-confidence, can communicate well and can operate high-tech equipment have the advantage of gaining a place in the job market.